Latex peptidases of Calotropis procera for dehairing of leather as an alternative to environmentally toxic sodium sulfide treatment - Lopez, Laura Maria Isabel (2017)
Dehairing of crude leather is a critical stage performed at the beginning of its processing to obtain industrially useful pieces. Tanneries traditionally apply a chemical process based on sodium sulfide. Since this chemical reactive is environmentally toxic and inefficiently recycled, innovative protocols for reducing or eliminating its use in leather depilation are welcomed. Therefore, latex peptidases from Calotropis procera (CpLP) and Cryptostegia grandiflora (CgLP) were assayed for this purpose. Enzyme activity on substrates representative of skin such as hide powder azure (UHPA), elastin (UE), azocollagen (UAZOCOL), keratin (UK), and epidermis (UEP) was determined, while depilation activity was assayed on cow hide. Only CpLP was active against keratin (13.4 UK) and only CgLP was active against elastin (0.12 UE). CpLP (93.0 UHPA, 403.6 UAZOCOL, 36.3 UEP) showed higher activity against the other substrates than CgLP (47.6 UHPA, 261.5 UAZOCOL, 8.5 UEP). In pilot assays, CpLP (0.05% w/v with sodium sulfite 0.6% w/v as activator) released hairs from cow hide pieces. Macroscopic and microscopic analyses of the hide revealed that the dehairing process was complete and the leather structure was preserved. The proteolytic system of C. procera is a suitable bioresources to be exploited by tanneries.